Plasma lens for electron and positron beams - Bondar, D.S.; Maslov, V.I.; Onishchenko, I.N.; Ovsiannikov, R.T. (Вопросы атомной науки и техники, 2021)
Focusing of both electron and positron bunches in electron-positron collider is necessary. When long electron/positron bunch is injected into the plasma, the focusing force is not uniform but oscillated. It is shown that a long positron bunch after focusing is destroyed faster than an electron bunch due to betatron and plasma oscillations.